2006
DOI: 10.1108/09596110610673556
|View full text |Cite
|
Sign up to set email alerts
|

Tour operators and alternative tourism in Italy

Abstract: PurposeThe paper sets out to analyses the approach of Southern Italian regions in the way they are developing different types of tourist products.Design/methodology/approachIn an attempt to measure tour operator preferences that impact the offer features, the tour operators' profiles have been traced, through a cluster analysis, in order to develop the market of new tourist products in Southern Italy.FindingsThe findings prove that the attitude of foreign tourists in choosing Southern Italian destinations is i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…However, they are still challenging to aggregate into a model wildly because the scope and definition might differ across destinations or countries relative to their development levels (Balan et al, 2009; World Economic Forum, 2010). Numerous variables could be used to determine the TC of any given country (Mazanec & Ring, 2011; Trunfio et al, 2006) if we connect these attributes into a systematic CM model to evaluate a national tourism competitiveness status without the examination of relevance and representativeness of construct of interest, it is problematic because many of the variables identified may neither comply with country-based tourism competitiveness nor relevant to country-based TC (Abreu Novais et al, 2018). For example, using the TTCI published by the WEF has been subject to methodological criticism, such as the arbitrary weighting of variables and using very simple methodologies; usually arithmetic means to measure the competitiveness of tourism destinations, where different indicators are given equal weight (Croes & Kubickova, 2013; Pulido-Fernández & Rodríguez-Díaz, 2016).…”
Section: Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…However, they are still challenging to aggregate into a model wildly because the scope and definition might differ across destinations or countries relative to their development levels (Balan et al, 2009; World Economic Forum, 2010). Numerous variables could be used to determine the TC of any given country (Mazanec & Ring, 2011; Trunfio et al, 2006) if we connect these attributes into a systematic CM model to evaluate a national tourism competitiveness status without the examination of relevance and representativeness of construct of interest, it is problematic because many of the variables identified may neither comply with country-based tourism competitiveness nor relevant to country-based TC (Abreu Novais et al, 2018). For example, using the TTCI published by the WEF has been subject to methodological criticism, such as the arbitrary weighting of variables and using very simple methodologies; usually arithmetic means to measure the competitiveness of tourism destinations, where different indicators are given equal weight (Croes & Kubickova, 2013; Pulido-Fernández & Rodríguez-Díaz, 2016).…”
Section: Literaturementioning
confidence: 99%
“…However, they are still challenging to aggregate into a model wildly because the scope and definition might differ across destinations or countries relative to their development levels (Balan et al, 2009;World Economic Forum, 2010). Numerous variables could be used to determine the TC of any given country (Mazanec & Ring, 2011;Trunfio et al, 2006) if we connect these attributes into a systematic CM model to evaluate a national tourism competitiveness status without the examination of relevance and representativeness of construct of interest, it is problematic because many of the variables identified may neither comply with country-based tourism competitiveness nor…”
Section: Determinants Of Tcmentioning
confidence: 99%
“…However, the lower knowledge barriers faced by domestic tourists can increase their day trips to locations close to the destination region (Paci & Marrocu, 2014). In addition, despite the role of the Internet in recent years (Nav ıo-Marco et al, 2018), most international tourism marketing maintains the traditional oligopolistic structure (G€ ossling, 2017;Trunfio et al 2006). This leads to tourist concentration through economies of scale and hence limits movements of tourists in less flexible itineraries, creating territorial tensions (Coccossis & Nijkamp, 1995;Lau & McKercher, 2006).…”
Section: Economic Growth Conditional Convergence Cohesion and Tourismmentioning
confidence: 99%
“…Wedding planners are identified as having a central role in coordinating the network of local companies providing the various wedding and tourism services, the local public authorities and, when necessary, religious bodies (Fortezza & Del Chiappa, 2012). In the context of the emergence of a new wedding destination, it can be suggested that wedding planners, not unlike tour operators, can act not only as coordinators but also as innovation drivers (Mattsson, Sundbo, & Fussing-Jensen, 2005;Rønning, 2010;Trunfio, Petruzzelli, & Nigro, 2006).…”
Section: Introductionmentioning
confidence: 99%